Systematic Systematic Literature Review: Model Predict-Observe-Explain (POE) dalam Pembelajaran Ilmu Pengetahuan Alam Jenjang Sekolah Menengah Pertama: Indonesia - Gusti Ayu Dewi Wismayani; Rai Sujanem; Ni Made Pujani (Jurnal Penelitian Pendidikan IPA, 2026)
Natural Sciences (IPA) plays an important role since elementary school as a foundation in developing students' logical, critical, and creative thinking skills. This study aims to examine the learning outcomes of science and the types of research used with the Predict–Observe–Explain (POE) learning model at the Junior High School (SMP) level through the Systematic Literature Review (SLR) method. The SLR method was carried out by searching scientific articles published between 2020 and 2025 through the Crossref and Scopus databases related to science learning outcomes and the types of research used in the application of the POE model. Inclusion criteria included articles discussing the implementation of the POE model in science learning at the junior high school level. Based on the analysis of the 13 articles reviewed, it can be concluded that the POE model can be implemented in various types of research, such as experiments, Classroom Action Research (CAR), Research and Development (R&D), and quantitative descriptive research. The results of the study indicate that the POE model contributes to science learning at the junior high school level, especially in improving students' scientific literacy and critical thinking skills. In addition, the POE model has also been proven effective in improving science learning outcomes, developing creative and analytical thinking skills, increasing learning motivation and improving students' communication skills.